51 Effect of a waiting room communication strategy on imaging rates and awareness of public health messages for low back pain in the emergency department. (8th June 2022) - Sharma, Sweekriti; Traeger, Adrian; Tcharkhedian, Elise; Middleton, Paul; Cullen, Louise; Maher, Chris
Abstract : Objectives: Imaging for low back pain in the Emergency Department is common. We know that patients and public have misconceptions about value of imaging. Strong public health messaging to address misconceptions about imaging has the potential to reduce desire for imaging. The effects of waiting room communication strategy on use of diagnostic imaging of low back pain are not clear. We aimed determined the effect of a waiting room communication strategy to increase awareness of potential harms of unnecessary imaging for low back pain on lumbar imaging rates in the emergency department (ED). Method: We conducted a controlled experimental study with BABA design, with a 6-week run-in time. This was followed by alternating one-week intervention and control periods. The Control group received standard waiting room messaging at the time (COVID-19 related messages), displayed on a 55' LCD screen. The Intervention group received a communication strategy (five posters and an information leaflet) describing the potential harms of unnecessary imaging for low back pain, shown on the same screen. The primary outcome was the number and proportion of patients presenting to ED with low back pain who received at least one lumbar imaging test. Secondary patient-reported outcomes were patient satisfaction, and awareness of campaign messages. Results: For the imaging outcome, 337 people presenting to ED with low back pain were included over a 4-month period (intervention n= 99; control n= 238). Use of lumbar imaging was 25% in those exposed to the communication strategy (95% CI= 18% to 35%) compared with 29% in those exposed to the standard waiting room messaging (95% CI= 23% to 35%) (OR= 0.83; 95% CI= 0.49 to 1.41). For the patient-reported outcomes, 349 patients presenting to ED for any condition responded to the survey (intervention n=170; control n=179; response rate =33%). There was uncertain evidence that the intervention increased awareness of the communication strategy Leaflet (OR= 2.00, 95% CI= 0.90 to 4.47). Other measures did not suggest between-group differences in patient satisfaction or awareness of the campaign messages. Conclusions: The waiting room communication strategy may slightly reduce the proportion of patients with low back pain who receive lumbar imaging; though there is uncertainty due to imprecision. The campaign did not appear to increase awareness of campaign messages or affect patient satisfaction in a sample of patients presenting to the ED for any reason. Larger studies should investigate whether simple, low-cost waiting room communication strategies can raise awareness of unnecessary healthcare and influence healthcare quality.